2016
DOI: 10.1186/s13584-016-0103-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with choice of approach for Group B streptococcus screening

Abstract: BackgroundThe crude rate of early-onset Group B streptococcus disease (EOGBS) in Israel has been consistently under 0.5 for 1000 live births for the past 8 years. The Israeli Ministry of Health has adapted the risk factor based approach for preventing EOGBS and universal bacteriological screening for GBS is not recommended. In spite of this policy, there are indications that many pregnant women in Israel undergo bacteriological screening for GBS.The objective of this study is to assess the rate and characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Increased rates of GBS EOD (0.51/1000 live births) and IUFD (3.79/1000 live births) in MHMC during 2017 led us to enhanced screening of pregnant woman before labor. We found that GBS carriage rates in MHMC were higher than the carriage rate reported in Israel (26.1% versus 6–21%, respectively) [ 4 , 24 ]. MHMC caters mostly Orthodox Jewish women.…”
Section: Discussionmentioning
confidence: 72%
“…Increased rates of GBS EOD (0.51/1000 live births) and IUFD (3.79/1000 live births) in MHMC during 2017 led us to enhanced screening of pregnant woman before labor. We found that GBS carriage rates in MHMC were higher than the carriage rate reported in Israel (26.1% versus 6–21%, respectively) [ 4 , 24 ]. MHMC caters mostly Orthodox Jewish women.…”
Section: Discussionmentioning
confidence: 72%
“…1 Nonetheless, about 30% of pregnant women in Israel undergo GBS screening. 6 Intrapartum real-time polymerase chain reaction (PCR) has demonstrated more sensitivity and specificity for intrapartum detection of GBS colonisation than risk-factor-based detection and universal GBS culture screening at 35-37 weeks. [7][8][9] A pilot study showed that 68% of women in labour who fulfilled the risk-factor criteria were GBS negative by PCR upon admission.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Streptococcus agalactiae (group B streptococcus, GBS), a common commensal of the female genital tract, has been considered the main cause of neonatal sepsis and meningitis and as the most common agent of invasive infections in pregnant women [1]. According to the previous studies in different countries, approximately 10.00%-31.50% of pregnant women are vaginally and/or rectally colonized with GBS [2][3][4][5][6]. The universal screening for maternal GBS colonization at 35 to 37 weeks' gestation and the use of intrapartum antibiotic prophylaxis have resulted in a nearly 80% reduction in the rate of neonatal GBS infection over the past 15 years, from 1.7 cases per 1,000 live births in the early 1990s to 0.34-0.37 cases per 1,000 live births in recent years [7].…”
Section: Introductionmentioning
confidence: 99%